2017
DOI: 10.1155/2017/7409873
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of High-Nb X80 Steel Weld Pipes for the Second West-to-East Gas Transmission Pipeline Project

Abstract: The mechanical properties of steel pipe have great effects on the integrality and operation safety of gas transmission pipeline. In order to reduce the cost of the steel pipe, the high-Nb X80 pipeline steels with the different alloying systems have been used in the Second West-to-East Gas Transmission Pipeline Project. Nevertheless, an investigation into the effects of chemical composition on the mechanical properties of steel pipes is lacking. In this work, the chemical composition and mechanical properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Bends are some of key parts of the pipeline projects [1,2]. Recently, in order to maximize the transport efficiency and decrease the construction and transposition costs, the gas pipeline transmission develops toward a larger diameter and/ or higher operation pressure; thereby, the high strength X80 steel grade and heavy-wall pipe over 22 mm have been applied to many long-distance transmission pipeline projects [3,4], such as the ird West-to-East Gas Transmission Pipeline Project and the Sino-Russian Gas Transmission Pipeline Project. Contemporaneously, heavy-wall hot bends have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Bends are some of key parts of the pipeline projects [1,2]. Recently, in order to maximize the transport efficiency and decrease the construction and transposition costs, the gas pipeline transmission develops toward a larger diameter and/ or higher operation pressure; thereby, the high strength X80 steel grade and heavy-wall pipe over 22 mm have been applied to many long-distance transmission pipeline projects [3,4], such as the ird West-to-East Gas Transmission Pipeline Project and the Sino-Russian Gas Transmission Pipeline Project. Contemporaneously, heavy-wall hot bends have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…In [24], the authors evaluated the mechanical properties of API 5L X80 pipes and concluded that the mechanical properties from different suppliers have a strong correlation with EC, especially TS and toughness. In the case of the steels used in this study, sample 3 came from a batch that presented ECPcm values slightly higher than the batch that originated sample 4.…”
Section: Resultsmentioning
confidence: 99%
“…With the rapid increase in demand for clean energy, such as natural gas, long-distance gas transportation pipelines are developing towards larger diameters and higher operating pressures to maximize transport efficiency, promoting the rapid development of high-strength pipeline steel. Thus, high-strength X80 grade steels have been applied in high-throughput long-distance gas transportation pipelines [ 1 , 2 , 3 ]. Although the traditional acicular ferrite (or low-carbon bainite) high-strength pipeline steels have good strength, toughness, and weldability balance, their plasticity does not meet the requirements of long-distance gas transportation pipelines to prevent deformation collapse caused by geological and ocean current movement in hazardous geological areas.…”
Section: Introductionmentioning
confidence: 99%